Exploring the role of polysaccharides from macroalgae in shaping gut microbiome and promoting anti-obesity outcomes - Mehdi Amiri Goushki; Zahra Kharat; Gustavo Waltzer Fehrenbach; Emma J. Murphy; Declan Devine; Noel Gately; Evert Fuemayor (Food Hydrocolloids, 2025)

Logistical considerations and challenges in deploying virtual biomethane pipelines to serve on-farm biogas plants - Dónal Ó Céileachair; Seán O'Callaghan; David M. Wall; David Goulding; Declan O'Connor; Jerry D. Murphy; Richard O'Shea (Journal of Cleaner Production, 2023)

Mapping myelin in white matter with T1-weighted/T2-weighted maps: discrepancy with histology and other myelin MRI measures - Stefano Sandrone; Marco Aiello; Carlo Cavaliere; Michel Thiebaut de Schotten; Katja Reimann; Claire Troakes; Istvan Bodi; Luis Lacerda; Serena Monti; Declan Murphy; Stefan Geyer; Marco Catani; et al. (Brain Structure and Function, 2023)
The ratio of T1-weighted/T2-weighted magnetic resonance images (T1w/T2w MRI) has been successfully applied at the cortical level since 2011 and is now one of the most used myelin mapping methods. However, no reports have explored the histological validity of T1w/T2w myelin mapping in white matter. Here we compare T1w/T2w with ex vivo postmortem histology and in vivo MRI methods, namely quantitative susceptibility mapping (QSM) and multi-echo T2 myelin water fraction (MWF) mapping techniques. We report a discrepancy between T1w/T2w myelin maps of the human corpus callosum and the histology and analyse the putative causes behind such discrepancy. T1w/T2w does not positively correlate with Luxol Fast Blue (LFB)-Optical Density but shows a weak to moderate, yet significant, negative correlation. On the contrary, MWF is strongly and positively correlated with LFB, whereas T1w/T2w and MWF maps are weakly negatively correlated. The discrepancy between T1w/T2w MRI maps, MWF and histological myelin maps suggests caution in using T1w/T2w as a white matter mapping method at the callosal level. While T1w/T2w imaging may correlate with myelin content at the cortical level, it is not a specific method to map myelin density in white matter.

Memantine treatment does not affect compulsive behavior or frontostriatal connectivity in an adolescent rat model for quinpirole-induced compulsive checking behavior - Milou Straathof; Erwin L. A. Blezer; Christel E. Smeele; Caroline van Heijningen; Annette van der Toorn; Jan K. Buitelaar; Jeffrey C. Glennon; Willem M. Otte; Rick M. Dijkhuizen; Jan Buitelaar; Saskia de Ruiter; Jilly Naaijen; et al. (Psychopharmacology, 2022)
Rationale Compulsivity often develops during childhood and is associated with elevated glutamate levels within the frontostriatal system. This suggests that anti-glutamatergic drugs, like memantine, may be an effective treatment. Objective Our goal was to characterize the acute and chronic effect of memantine treatment on compulsive behavior and frontostriatal network structure and function in an adolescent rat model of compulsivity. Methods Juvenile Sprague–Dawley rats received repeated quinpirole, resulting in compulsive checking behavior ( n = 32; compulsive) or saline injections ( n = 32; control). Eight compulsive and control rats received chronic memantine treatment, and eight compulsive and control rats received saline treatment for seven consecutive days between the 10th and 12th quinpirole/saline injection. Compulsive checking behavior was assessed, and structural and functional brain connectivity was measured with diffusion MRI and resting-state fMRI before and after treatment. The other rats received an acute single memantine (compulsive: n = 12; control: n = 12) or saline injection (compulsive: n = 4; control: n = 4) during pharmacological MRI after the 12th quinpirole/saline injection. An additional group of rats received a single memantine injection after a single quinpirole injection ( n = 8). Results Memantine treatment did not affect compulsive checking nor frontostriatal structural and functional connectivity in the quinpirole-induced adolescent rat model. While memantine activated the frontal cortex in control rats, no significant activation responses were measured after single or repeated quinpirole injections. Conclusions The lack of a memantine treatment effect in quinpirole-induced compulsive adolescent rats may be partly explained by the interaction between glutamatergic and dopaminergic receptors in the brain, which can be evaluated with functional MRI.

A review of American lobster (Homarus americanus) records around the British Isles: 2012 to 2018 - Christopher John Barrett; Alastair Cook; David Stone; Chris Evans; Debbie Murphy; Paul Johnson; Marc Thain; Gabrielle Wyn; Mark Grey; Hugh Edwards; Declan Quigley; Paul Douglas Stebbing (Hydrobiologia, 2020)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

Does size matter for horny beetles? A geometric morphometric analysis of interspecific and intersexual size and shape variation in Colophon haughtoni Barnard, 1929, and C. kawaii Mizukami, 1997 (Coleoptera: Lucanidae) - Thea Eldred; Carlo Meloro; Clarke Scholtz; Declan Murphy; Katie Fincken; Matt Hayward (Organisms Diversity & Evolution, 2016)

Inverse fluoxetine effects on inhibitory brain activation in non-comorbid boys with ADHD and with ASD - Kaylita Chantiluke; Nadia Barrett; Vincent Giampietro; Paramala Santosh; Michael Brammer; Andrew Simmons; Declan G. Murphy; Katya Rubia (Psychopharmacology, 2015)

Autism spectrum disorders - an emerging area in psychopharmacology - Thomas Steckler; Will Spooren; Declan Murphy (Psychopharmacology, 2014)

Psychopharmacological prescriptions for people with autism spectrum disorder (ASD): a multinational study - Yingfen Hsia; Angel Y. S. Wong; Declan G. M. Murphy; Emily Simonoff; Jan K. Buitelaar; Ian C. K. Wong (Psychopharmacology, 2014)

Pharmacological treatments prescribed to people with autism spectrum disorder (ASD) in primary health care - Macey L. Murray; Yingfen Hsia; Karen Glaser; Emily Simonoff; Declan G. M. Murphy; Philip J. Asherson; Hanna Eklund; Ian C. K. Wong (Psychopharmacology, 2014)
Rationale Autism spectrum disorders (ASDs) affect 1 % of children, having significant impact on health and social outcomes. Psychotropic medication use by individuals with ASD in the USA increased over time, and polypharmacy occurred in >50 % of those prescribed. In the UK, no psychotropic drugs are approved in ASDs, and little is known about patterns of pharmacological treatment in the ASD population and associated co-morbidities. Methods We used The Health Improvement Network, a nationally representative primary care database, to assess the prevalence of ASD diagnoses, psychotropic drug prescribing and neuropsychiatric co-morbidities of 0–24 year olds between 1992 and 2008. Results ASD prevalence increased 65-fold from 0.01 % (1992) to 0.50 % (2008). Psychotropic drugs were prescribed to 29 % (1,619/5,651) of the ASD cohort; the most prescribed drugs were sleep medication (9.7 % of prescribed patients), psychostimulants (7.9 %) and antipsychotics (7.3 %). More patients were given psychostimulants and sleep medications over time from 1.5–6.3 % and 2.2–5.9 % respectively. Thirty-seven per cent of the cohort had ≥1 record of a neuropsychiatric co-morbidity, the most common being developmental difficulties and learning disabilities (12.6 %), behavioural, conduct and personality disorders (11.1 %) and attention deficit hyperactivity disorder (7.5 %). Conclusions British physicians are more conservative in prescribing practice than American colleagues. However, use of psychostimulants and antipsychotics is much higher in those with ASD than in the general population. Polypharmacy was seen in 34 % of prescribed patients in 2008. Additional studies examining use, efficacy, and long-term safety of antipsychotics and psychostimulants in autistic individuals are warranted.

Aripiprazole in the treatment of challenging behaviour in adults with autism spectrum disorder - Iain Jordan; Dene Robertson; Marco Catani; Michael Craig; Declan Murphy (Psychopharmacology, 2012)

Hippocampal Proton MR Spectroscopy in Early Alzheimer’s Disease and Mild Cognitive Impairment - Catherine M. L. Foy; Eileen M. Daly; Amanda Glover; Ruth O’Gorman; Andrew Simmons; Declan G. M. Murphy; Simon Lovestone (Brain Topography, 2011)

Effects of acute tryptophan depletion on neural processing of facial expressions of emotion in humans - Eileen Daly; Quinton Deeley; Brian Hallahan; Michael Craig; Michael Brammer; Melissa Lamar; Anthony Cleare; Vincent Giampietro; Christine Ecker; Lisa Page; Fiona Toal; Mary L. Phillips; et al. (Psychopharmacology, 2010)